A magnesium@high-sulfur coke hydrogen storage material and preparation method thereof

Through high sulfur coke grinding and pressure melting permeability and condensation technology, the high temperature and poor stability of magnesium hydrogen storage materials are solved, and the low-temperature and efficient hydrogen storage of magnesium@high sulfur coke hydrogen storage materials is achieved, which improves the load of nanomagnesium rate and cycle performance.

CN118419854BActive Publication Date: 2024-12-17SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410486481.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2024-12-17
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

The hydrogen absorption and release platform of magnesium hydrogen storage materials is high in temperature and slow in kinetics, and the particle size is unstable after nano-narcotics, which is easy to oxidize, which limits its application; the matrix preparation procedure is complex, and the adsorption effect of functional carbon pores on liquid phase magnesium is weak, Causes waste of magnesium resources.

Method used

High sulfur coke is used as a grinding agent and magnesium powder mixed with ball milling. Through pressure melting and adsorption condensation methods, magnesium@high sulfur coke hydrogen storage materials are formed. The defined pore structure and surface properties of high sulfur coke are used to achieve solidification of magnesium. The stage limit and regeneration of the three phases of liquid and gas.

Benefits of technology

It significantly improves the nanoscale effect and load rate of magnesium, reduces the platform temperature, improves the hydrogen absorption and discharge rate and cycle stability, avoids oxidation and agglomeration of magnesium, and achieves low-temperature and efficient reversible hydrogen storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118419854B_ABST
    Figure CN118419854B_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium@high-sulfur coke hydrogen storage material and a preparation method thereof, comprising the following steps: mixing magnesium powder and high-sulfur coke in an inert atmosphere and ball milling to obtain a mixture; pressing the mixture into tablets, heating and infiltrating in an inert atmosphere to obtain an infiltration product and magnesium vapor; and adsorbing and condensing the magnesium vapor on the prepared infiltration product to obtain the magnesium@high-sulfur coke hydrogen storage material. The prepared magnesium@high-sulfur coke has the advantages of low platform temperature, high hydrogen storage capacity, fast hydrogen absorption and desorption rate, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen storage materials, and specifically provides a magnesium@high-sulfur coke hydrogen storage material and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] As an ideal high-density hydrogen storage material, magnesium is abundant in reserves, low in cost, and lightweight, and is one of the future development directions for high-density storage. However, the high platform temperature and slow kinetics of hydrogen absorption and desorption of magnesium hydrogen storage materials, as well as the active chemical properties of magnesium (the surface is easily oxidized to form a magnesium oxide film), limit its application. Magnesium nano-crystallization can significantly improve the hydrogen absorption and desorption characteristics of magnesium-based systems, but it faces problems such as poor particle size stability and cycle performance, and is very easy to aggregate and grow during activation, phase flow, friction, and thermal effects of hydrogen absorption and desorption, and then deactivate.

[0004] The use of functional carbon such as carbon nanotubes as the matrix to nano-confine molten liquid magnesium to prepare nano-magnesium-based hydrogen storage materials is considered to be one of the effective technical means to solve the problem due to the physical isolation and confinement of nano-magnesium particles, as well as the matrix's specific charge transfer, lubrication, defect structure and other catalytic effects. However, the following problems need to be further overcome: First, the matrix preparation procedure is complicated and the process is difficult, which seriously limits its promotion and application; second, the "molecular straw" effect of the functional carbon pores on liquid magnesium is weak, and the magnesium content in the pores is low; third, there is a problem of magnesium evaporation and escape during the confinement process, resulting in serious waste of magnesium resources. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a magnesium@high-sulfur coke hydrogen storage material and a preparation method thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a magnesium@high-sulfur coke hydrogen storage material, comprising the following steps:

[0008] Mixing magnesium powder and high-sulfur coke in an inert atmosphere and ball milling to obtain a mixture;

[0009] After the mixture is pressed into sheets, it is heated and melt-infiltrated in an inert atmosphere to obtain a melt-infiltrated product and magnesium vapor;

[0010] The prepared infiltration product is subjected to adsorption and condensation of magnesium vapor to obtain magnesium@high sulfur coke hydrogen storage material.

[0011] The specific confinement process consists of three stages. First, high-sulfur coke with a limited pore distribution structure is used as a grinding aid. It is mixed with magnesium powder and ball-milled to obtain a nano-magnesium source of a predetermined size. This completes the first-stage design of "gaps to accommodate solid-phase nano-magnesium particles" and constructs a "solid-phase" nano-magnesium source network with a high surface atomic ratio.

[0012] Secondly, by utilizing pressure infiltration to melt the solid-phase magnesium particles, they enter the nanopores of the matrix through the "molecular straw" effect and achieve physical isolation, completing the second level of "pore-filled liquid-phase nanomagnesium droplets" and strengthening the "molecular straw" effect of the micro-nano pores on the nanomagnesium droplets.

[0013] Finally, the escaped magnesium vapor enters the temperature and pressure controlled adsorption condensation bed, penetrates the built-in magnesium@high-sulfur coke particle bed, and is again adsorbed and condensed by the system's massive surface, completing the third stage of "surface adsorption condensation of magnesium vapor" and storing the escaped magnesium vapor again.

[0014] Using high-sulfur coke as a nano-confined matrix, the three phases of magnesium "solid, liquid, and gas" are confined in the "gap, pore, and surface" space of the matrix. The prepared magnesium@high-sulfur coke has the advantages of low platform temperature, high hydrogen storage capacity, and fast hydrogen absorption and desorption rate.

[0015] In some embodiments, the high-sulfur coke is prepared by mixing high-sulfur petroleum coke and alkali in proportion, calcining, activating and carbonizing the mixture in an inert atmosphere, neutralizing the mixture with acid, washing the mixture with clean water and drying the mixture.

[0016] High-sulfur coke is produced based on the desulfurization activation method of alkali metal compounds, combined with multi-solvent and multi-atmosphere activation, and its pore distribution structure and surface properties are prepared in a targeted manner.

[0017] Alkali is used for desulfurization and pore activation. The type of solvent can be water or an organic reagent such as ethanol, etc. The atmosphere refers to the carrier gas component, which can be water vapor, carbon dioxide, nitrogen, ammonia, sulfur dioxide, etc.

[0018] Preferably, the base is KOH or NaOH.

[0019] Preferably, the mass ratio of high sulfur petroleum coke to alkali is 1:2-5.

[0020] Preferably, the temperature of calcination activation and carbonization in an inert atmosphere is 900-1000° C., and the time is 0.5-1.5 h, preferably 1 h.

[0021] Further preferably, the heating rate during the activation and carbonization process is 3-8°C / min, preferably 5°C / min.

[0022] Preferably, the acid is hydrochloric acid, sulfuric acid, phosphoric acid or nitric acid.

[0023] In some embodiments, the mass ratio of magnesium powder to high-sulfur coke is 9:1 to 20:1.

[0024] Preferably, the ball-to-material ratio during ball milling is 40 to 50:1.

[0025] Preferably, the ball milling time is 5-7h.

[0026] In some embodiments, the tableting is to put the mixture into a tableting mold and press it at 20-40 MPa for 0.5-1.5 hours. The mixture of nano-magnesium metal and high-sulfur coke is prepared for tableting, which increases the contact area between magnesium and high-sulfur coke and effectively shortens the diffusion path and resistance of magnesium melt.

[0027] Preferably, the tabletting pressure is 30 MPa and the pressing time is 1 h.

[0028] In some embodiments, the infiltration temperature is 656-711°C and the infiltration time is 7-85 min. Preferably, the infiltrated material is cooled at a cooling rate of 3-10°C / min, and when the temperature drops to 300-400°C, the inert atmosphere is replaced with a hydrogen atmosphere to prevent oxidation and also allow magnesium to generate magnesium hydride for safe retention.

[0029] Further preferably, when the temperature of the material is about to reach 200° C., programmed cooling is started to decrease to 70-90° C., and the hydrogen atmosphere is replaced by an inert atmosphere.

[0030] More preferably, the programmed cooling rate is 5-10°C / min.

[0031] In some embodiments, the adsorption condensation is performed in an adsorption condensation bed, the pressed sheet is fixed on the sand core of the condensation bed, and then the magnesium vapor generated during the infiltration process is introduced into the bed to adsorb the magnesium vapor;

[0032] During the adsorption process, circulating cooling water is introduced into the outer layer of the condensation bed for condensation.

[0033] When the adsorption condensation is finished, the product condensation surface condenses into nano-magnesium crystals, and finally the sample can be taken out.

[0034] In a second aspect, the present invention provides a magnesium@high-sulfur coke hydrogen storage material prepared by the preparation method.

[0035] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0036] 1. The nanoscale effect of magnesium is significantly improved. The ball milling of high-sulfur coke aids the production of nano-magnesium grains of suitable size, laying the foundation for strengthening the "molecular straw" effect of nanopores on magnesium droplets; the escaped magnesium vapor is again adsorbed and condensed into nano-magnesium crystals by the massive surface of the system, and the nanoscale effect is obvious.

[0037] 2. The confined storage effect of magnesium clusters is remarkable. With the manufactured massive gaps, pores and surfaces as the confined space and the same level of nano-magnesium source as the guarantee, the three phases of magnesium "gas, liquid and solid" are orderly stored in the corresponding confined space, which has a significant effect on improving the magnesium loading rate.

[0038] 3. The system has high cycle stability. The three-level spatial nano-confinement achieves effective physical isolation of Mg / MgH2 clusters, which can effectively prevent them from being oxidized and contaminated, and from subsequent agglomeration and growth. The thermodynamic performance of hydrogen absorption and desorption of the material is significantly improved.

[0039] 4. The material has excellent performance and great potential for use. The magnesium @ high-sulfur coke hydrogen storage material is synthesized by ball milling-melt infiltration-adsorption condensation nano-confinement of the three phases of magnesium "solid, liquid, and gas", achieving reversible hydrogen absorption and desorption at <100°C and close to the hydrogen storage capacity of rare earth materials, which is expected to build a low-cost, large-scale, low-temperature and cheap magnesium-based composite hydrogen storage material with practical potential.

[0040] High-sulfur petroleum coke is a major by-product of the delayed coking process with a high carbon content. It is a potential high-quality and low-cost carbon precursor. Porous carbon made from high-sulfur coke (referred to as high-sulfur coke) has great potential as a substitute for functional carbon nanoconfined matrices such as carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0042] Figure 1 This is a schematic diagram of the principle of the magnesium@high sulfur coke hydrogen storage material of the present invention;

[0043] Figure 2 The flow chart of preparing magnesium@high sulfur coke hydrogen storage material of the present invention;

[0044] Figure 3 This is a data diagram of magnesium loading rate in magnesium@high sulfur coke hydrogen storage material according to Example 2 of the present invention;

[0045] Figure 4 This is a schematic diagram of a temperature and pressure controlled adsorption condensation bed according to Example 3 of the present invention;

[0046] Figure 5 This is a comparison chart of the effects of preparing magnesium@high sulfur coke hydrogen storage materials in Example 1 and Example 3 of the present invention.

[0047] In the figure, 1-air inlet; 2-frosted port plug; 3-water outlet; 4-sand core; 5-water inlet; 6-air outlet. DETAILED DESCRIPTION

[0048] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0049] The present invention will be further described below in conjunction with the embodiments.

[0050] Unless otherwise specified, the materials used in the examples and comparative examples can be obtained through commercial channels.

[0051] Example 1

[0052] A method for preparing a magnesium@high sulfur coke hydrogen storage material, the flow chart is shown in Figure 2 ,include:

[0053] Step 1: Preparation of high sulfur coke;

[0054] 11) Mix high-sulfur petroleum coke and KOH in a mass ratio of 1:5, perform chemical activation and high-temperature carbonization in a tubular furnace under the protection of high-purity argon, increase the temperature to 1000° C. at a heating rate of 5° C. / min, maintain the constant temperature for 1 hour, and cool to room temperature for use;

[0055] 12) adding 1 mol / L HCl solution to the prepared high-sulfur coke to neutralize and adjust the pH to 7;

[0056] 13) Finally, the high-sulfur coke is filtered, washed, and dried multiple times to obtain the final sample.

[0057] Step 2: ball milling magnesium and high-sulfur coke;

[0058] 21) Magnesium powder (0.56 g) and high-sulfur coke powder (0.06 g, as a grinding aid) were placed in a ball mill and ball milled under an argon atmosphere with a ball-to-material ratio of 40:1;

[0059] 22) The total ball milling time is 6 hours, with 30 minutes of forward rotation, 30 minutes of reverse rotation, 10 minutes of rest time, and a rotation speed of 400 rpm. Finally, take out the ball mill and mix the sample.

[0060] Step 3: tableting;

[0061] 31) Take 0.1g high sulfur coke and 0.3g mixed ball milled sample and put them into a tableting mold, and press at 30MPa for 1h;

[0062] 32) Prepare a mixture of nano-magnesium metal and high-sulfur coke to form tablets, increase the contact area between magnesium and high-sulfur coke, effectively shorten the diffusion path and resistance of magnesium melt, and finally take out cylindrical tablets.

[0063] Step 4: Infiltration:

[0064] 41) The pellet prepared in step 3 is placed in a tube furnace protected by an argon atmosphere and sintered at a high temperature at a heating rate of 5°C / min;

[0065] 42) The temperature was increased from 20°C to 666°C and maintained for 22 min;

[0066] 43) Then the temperature starts to decrease, and the cooling rate during the cooling process is still 5°C / min. When the temperature drops to about 360°C, the argon atmosphere is replaced by H2 gas flow;

[0067] 44) After 200°C, the temperature was programmed to cool down, and when it dropped to about 80°C, the atmosphere was switched to argon to discharge the remaining H2 in the tube furnace, and finally the sample was taken out.

[0068] Based on KOH carbonization-activation method, a specific surface area of ​​856.3m 2 / g, 0.7cm 3 / g, an average pore size of 3.3nm and a micropore ratio of <6nm accounting for ~50%, successfully obtained a magnesium-based hydrogen storage material with a hydrogen storage rate of 0.6wt.% and reversible hydrogen absorption and desorption at 100℃.

[0069] The composite hydrogen storage material prepared in the above embodiment is characterized. The BET test technology can be used to obtain analytical data such as the specific surface area and pore volume of the material. The volume difference before and after infiltration can be calculated by the formula to infer the magnesium loading rate. The formula is as follows:

[0070] η=(M1V1-M2V2)ρ Mg / [(M1V1-M2V2)ρ Mg +M c ];

[0071] in:

[0072] M1, M2-the mass before and after infiltration, g;

[0073] V1, V2-pore volume before and after infiltration, cm 3 / g;

[0074] ρ Mg - is the density of magnesium, 1.74 g / cm 3 ;

[0075] M c - is the mass of high sulfur petroleum coke activated carbon, g.

[0076] The magnesium loading rate of the prepared hydrogen storage material is calculated to be 36%. The reason is that the evaporation temperature of the nano-magnesium clusters in the <6nm pores is much lower than the phase transition temperature of 940±10K for the gap to accommodate the melting of ~70nm magnesium particles and then capillary to micro-pores, resulting in the synchronous evaporation of magnesium in the pore volume, and the scale effect of the remaining gap accommodating 20~40nm magnesium particles and ~10nm pores is weakened.

[0077] Example 2

[0078] The preparation method of the composite hydrogen storage material of this embodiment is the same as that of embodiment 1 except step 1 and step 4, and the other conditions and steps 2-3 are the same as those of embodiment 1.

[0079] Step 1:

[0080] 11) Mix high-sulfur petroleum coke and KOH in a mass ratio of 1:5, soak them in 90% anhydrous ethanol and 10% deionized water and ultrasonicate them for 2 hours, then take them out and dry them at 120° C. for later use;

[0081] 12) Carry out chemical activation and high-temperature carbonization in a tube furnace under the protection of high-purity argon gas, increase the temperature to 1000°C or 900°C at a heating rate of 5°C / min, maintain the constant temperature for 1 hour, and cool to room temperature for use;

[0082] 13) Add 1 mol / L HCl solution to the prepared high-sulfur coke to neutralize and adjust the pH to 7;

[0083] 14) Finally, the high-sulfur coke is filtered, washed, and dried multiple times to obtain the final sample.

[0084] Step 4: Infiltration:

[0085] 41) The pellet prepared in step 3 is placed in a tube furnace protected by an argon atmosphere and sintered at a high temperature at a heating rate of 5°C / min;

[0086] 42) The temperature was increased from 20°C to 636°C, 651°C, 666°C, 681°C, 696°C and 711°C respectively, and the infiltration time was maintained for 22 min;

[0087] 43) Then the temperature starts to decrease, and the cooling rate during the cooling process is still 5°C / min. When the temperature drops to about 360°C, the argon atmosphere is replaced by a hydrogen flow;

[0088] 44) After 200°C, the temperature was programmed to cool down, and when it dropped to about 80°C, the argon atmosphere was switched to discharge the remaining hydrogen in the tube furnace, and finally the sample was taken out.

[0089] Depend on Figure 3It can be seen that the magnesium loading rate of Mg@high-sulfur coke based on high-sulfur coke (C(1000)) prepared at 1000℃ is the highest, reaching 38%, while the Mg loading rate of the composite hydrogen storage material infiltrated with high-sulfur coke soaked in alkali solution (C(1000 alkali solution)) is the lowest, only 29%.

[0090] Therefore, the effect of the infiltration temperature on the Mg loading rate was investigated based on Example 1. As can be seen from the figure, with the increase of the infiltration temperature, the Mg loading rate shows a trend of first increasing and then decreasing, and the Mg loading rate is the highest at 666°C.

[0091] Example 3

[0092] A method for preparing a Mg@high-sulfur coke hydrogen storage material. In this example, the composite hydrogen storage material is additionally added with step 5, and the remaining conditions and steps 1-4 are the same as those in Example 1, including:

[0093] Step 5:

[0094] 51) Based on the evaporation of magnesium vapor in the aforementioned step 4, the infiltration sample prepared in step 4 is placed at the 1 / 2 sand core of a temperature-controlled and pressure-controlled adsorption condensation bed protected by an argon atmosphere, as shown in FIG. Figure 4 As shown, the magnesium vapor evaporated in step 4 is passed into the adsorption condensation bed along with argon atmosphere, and the argon flow rate is 150ml / min; the outer layer of the condensation bed is circulating cooling water, which enters from the bottom and exits from the top, has a temperature of 20°C and a flow rate of 500ml / min; the adsorption condensation is completed again, and finally the sample is taken out.

[0095] The magnesium loading rate of the prepared hydrogen storage material is 65%.

[0096] Depend on Figure 5 It can be seen that when the infiltration temperature increases from 636℃ (Infiltration method 1) to 666℃ (Infiltration method 2), the capillary filling effect of magnesium droplets is obvious, the unit pore volume decreases sharply, and the reduction rate of pore volume <2nm and 4-8nm is relatively large; when the temperature is increased to 711℃, the pore volume of the system increases instead of decreases, which is due to the fact that almost all of the small-scale nano-magnesium evaporates during the confined synthesis process. After adopting the three-level confined loading method of magnesium@high-sulfur coke hydrogen storage material, a significant change has been achieved compared with the initial effect.

[0097] In summary, the present invention successfully uses high-sulfur coke to load nano-metal magnesium. For solid-phase magnesium, its particle size is controlled to increase its surface atomic ratio. The premise is that the same nano-scale magnesium is obtained by ball milling matching. In the process of ball milling nano-magnesium, an appropriate proportion of high-sulfur coke is added as a grinding aid to prevent the agglomeration and growth of magnesium during the ball milling process, which greatly improves the ball milling efficiency. Its lubricating effect is conducive to the formation of small-sized magnesium particles, so that magnesium ball milling can more fully obtain nano-magnesium. For molten liquid phase magnesium, through the effects of capillary force, van der Waals force, etc., it continuously and spontaneously enters the low-concentration and huge micropores connected to it from the high-concentration mesopores and meso-macropores. The nano-magnesium in the pores is not easy to agglomerate and grow, and is firmly confined within the pore range of high-sulfur petroleum coke activated carbon, thereby effectively overcoming the instability of nano-magnesium. For magnesium vapor, its partial pressure and relative concentration are regulated, and the pressure, bed temperature and temperature gradient in the adsorption condensation bed are changed to control its adsorption and collision and fully condense into nuclei to form small-grained nano-magnesium fine crystals during bed penetration. The thermodynamic properties of the prepared magnesium@high sulfur coke hydrogen storage material were significantly improved.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a magnesium@high-sulfur coke hydrogen storage material, characterized in that: The steps include: Mixing magnesium powder and high-sulfur coke in an inert atmosphere and ball milling to obtain a mixture; After the mixture is pressed into sheets, it is heated and melt-infiltrated in an inert atmosphere to obtain a melt-infiltrated product and magnesium vapor; The prepared melt infiltration product is subjected to adsorption and condensation of magnesium vapor to obtain magnesium@high sulfur coke hydrogen storage material; The preparation method of the high-sulfur coke is as follows: high-sulfur petroleum coke and alkali are mixed in proportion, calcined, activated and carbonized in an inert atmosphere, then neutralized with acid, washed with clean water and dried to obtain the high-sulfur coke; The mass ratio of magnesium powder to high sulfur coke is 9:1~20:1; The tableting comprises placing the mixture into a tableting mold and pressing at 20-40 MPa for 0.5-1.5 h; The base is KOH or NaOH; The mass ratio of high sulfur petroleum coke to alkali is 1:2-5; The calcination activation and carbonization temperature in an inert atmosphere is 900-1000°C and the time is 0.5-1.5h; The heating rate during activation and carbonization is 3-8°C / min; The adsorption condensation is carried out in an adsorption condensation bed, the pressed sheet is fixed on the sand core of the condensation bed, and then the magnesium vapor generated during the infiltration process is introduced into the bed to adsorb the magnesium vapor; During the adsorption process, circulating cooling water is introduced into the outer layer of the condensation bed for condensation.

2. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 1, characterized in that: The acid is hydrochloric acid, sulfuric acid, phosphoric acid or nitric acid.

3. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 1, characterized in that: The ball-to-material ratio during ball milling is 40~50:1; The ball milling time is 5-7h.

4. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 1, characterized in that: The tableting pressure was 30 MPa and the pressing time was 1 h.

5. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 1, characterized in that: The infiltration temperature is 656-711°C, and the infiltration time is 7-85min.

6. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 1, characterized in that: The infiltrated material is cooled at a cooling rate of 3-10°C / min. When the temperature drops to 300-400°C, the inert atmosphere is replaced by a hydrogen atmosphere.

7. The method for preparing the magnesium@high sulfur coke hydrogen storage material according to claim 6, characterized in that: When the temperature of the material drops to 200°C, start program cooling to 70-90°C, and replace the hydrogen atmosphere with an inert atmosphere; The rate of programmed cooling is 5-10°C / min.

8. A magnesium@high sulfur coke hydrogen storage material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.